THE PROSPECTS FOR INSTITUTIONAL REFORMS OF THE EUROPEAN UNION: A LIBERAL INTERGOVERNMENTALIST PERSPECTIVE - Piotr Tosiek (Srpska Politička Misao)
The purpose of the article is to determine the probability of institutional reforms resulting from the debate on EU future held as a part of the “Conference on the Future of Europe” initiated in 2020. In the theoretical dimension, the analysis is based on the application of the liberal intergovernmentalist approach with its three assumptions: the strict categorization of intergovernmental decision-making built on the triad ‘preferences-negotiations-institutions’, the concept of demoicracy, and the need for differentiated integration. On this basis, three hypotheses for each reform are presented and verified, which leads to determination of their possible implementation. The main thought is the statement that, when adopting the liberal intergovernmentalism, the EU will remain an intergovernmental organization, founded on societies organized in nation states, but at the same time internally differentiated in terms of the quality of membership.